2022
DOI: 10.52366/edusoshum.v2i3.47
|View full text |Cite
|
Sign up to set email alerts
|

Character Education Metod From the Lens of Al-Ghazali on Generation Z

Abstract: The moral significance of Generation Z pupils is the issue in this study. This is illustrated by the numerous activities outside the norm displayed by Generation Z students, including using educational drugs, student brawls, and a lack of respect for lecturers, parents, and even society. This is due to using and applying an ineffective value education strategy for kids. Researchers will look at how to teach the values of the Al-Ghazali method to generation Z in this project. This research aims to describe Al-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Parents should assess each child's learning capacity and potential before planning their education. Al-Ghazali proposed that teachers should "speak to men according to their cognitive level, using pictures and examples," to facilitate effective instruction (Sasmita, 2022).…”
Section: Al-ghazali's Concept Of Educationmentioning
confidence: 99%
“…Parents should assess each child's learning capacity and potential before planning their education. Al-Ghazali proposed that teachers should "speak to men according to their cognitive level, using pictures and examples," to facilitate effective instruction (Sasmita, 2022).…”
Section: Al-ghazali's Concept Of Educationmentioning
confidence: 99%
“…This is similar to the results of several researchers' research on cases found in several articles which reveal that the widespread cases of bullying against classmates make victims who can no longer stand it choose to drop out of school and even the worst case ends their lives by committing suicide (Schihalejev et al, 2020). Apart from that, other cases were found, such as the many acts outside the norm displayed by students in the Generation Z era, starting from educational drug use, student brawls, and a lack of respect for lecturers, parents, and even the community where they live (Sasmita, 2022). This is not in accordance with the Q.S.…”
Section: Introductionmentioning
confidence: 99%